Measuring social return on business support for people at risk of social exclusion by SROI analysis - Krátký, Jiří (Univerzita Pardubice, 2010)
The paper contains introduction into the problems of the social return on investment analysis measured by the SROI method and the basic resources of, in the Czech Republic brand new, problems of measuring benefits of business support provided to people at risk of social exclusion. Use of the SROI analysis for measuring social benefits of business support is exemplified in the German project of “enterability”.
Keywords: socially responsible investment; social return on investment; SROI; business guidance